Environmental risk factors for autism - Dietert, Rodney R.; Dietert, Janice M.; DeWitt, Jamie C. (My University, 2011)
Autism is a devastating childhood condition that has emerged as an increasing social concern just as it has increased in prevalence in recent decades. Autism and the broader category of autism spectrum disorders are among the increasingly seen examples in which there is a fetal basis for later disease or disorder. Environmental, genetic, and epigenetic factors all play a role in determining the risk of autism and some of these effects appear to be transgenerational. Identification of the most critical windows of developmental vulnerability is paramount to understanding when and under what circumstances a child is at elevated risk for autism. No single environmental factor explains the increased prevalence of autism. While a handful of environmental risk factors have been suggested based on data from human studies and animal research, it is clear that many more, and perhaps the most significant risk factors, remain to be identified. The most promising risk factors identified to date fall within the categories of drugs, environmental chemicals, infectious agents, dietary factors, and other physical/psychological stressors. However, the rate at which environmental risk factors for autism have been identified via research and safety testing has not kept pace with the emerging health threat posed by this condition. For the way forward, it seems clear that additional focused research is needed. But more importantly, successful risk reduction strategies for autism will require more extensive and relevant developmental safety testing of drugs and chemicals.
Keywords: autism, autism spectrum disorders, drugs, environmental chemicals, infections, vaccinations, stressors, critical windows of development, developmental neurotoxicity testing